Influence of different priming treatments on germination potential and seedling establishment of four important hemp (Cannabis sativa L.) cultivars - Saba Latif; Rahmatullah Qureshi; Abdul Rauf; NoshinIlyas; Qaiser Hussain; Syed Sabir Hussain Shah; Sabith Rehman; Arshad Mahmood Khan; Nasrullah Khan; Mostafa A. Abdel-Maksoud; Abdul Malik; Sabiha Fatima; et al. (Scientific Reports)
Abstract Medicinal hemp (Cannabis sativa L.) is gaining popularity due to its natural products with potential therapeutic properties, and its cultivation has recently been initiated in developing countries such as Turkey, Iran, India, and Pakistan. The crop is primarily grown using feminized seeds or popular varieties to achieve higher cannabidiol (CBD) yields, with seeds costing approximately $5–10 each. However, limited knowledge exists on hemp seed germination under different seed priming techniques and variations in seedling growth parameters such as root and shoot lengths, as well as the influence of in vitro germination and growth in soil and cocopeat media. This study hypothesizes that various seed priming methods could significantly enhance hemp seed germination and different growth media may distinctly impact seedling growth of the tested cultivars. To test this, the study evaluated four cultivars/chemovars (viz., Fedora-17, Finola, CBD Pink Kush, and a local variety, Gulistan) under five seed priming treatments: indole butyric acid (IBA), moringa leaf extract, KNO3, hydro-priming, and a control (no priming). A randomized complete block design (RCBD) was used, and experimental data (in triplicate) were analyzed through analysis of variance (ANOVA) using a time-to-event approach. The findings revealed that IBA significantly (p < 0.05) improved seed germination rates, with CBD Pink Kush achieving the highest germination response (83%) among the tested cultivars. Furthermore, cocopeat demonstrated superior performance as a seedling growth medium across all cultivars, indicating its potential for hemp cultivation practices. This pioneering study provides a baseline for understanding hemp seed germination and seedling growth under different priming and growth media conditions, offering valuable insights for future research aimed at industrial and medicinal hemp production.